Application of culture-dependent and culture-independent methods for the identification of Lactobacillus kefiranofaciens in microbial consortia present in kefir grains - Hamet, Maria Fernanda (2013)
The biological and technological characteristics of kefiran as well as its importance in grain integrity led us to analyze the microbial kefir grain consortium with focus on Lactobacillus kefiranofaciens. The presence of L. kefiranofaciens in the nine kefir grains studied was demonstrated by denaturing gradient gel electrophoresis. By culture dependent methods applying a methodology focused on the search of this species, 22 isolates with typical morphology were obtained and identified applying a combination of SDS-PAGE of whole cell proteins, (GTG)5-PCR and sequence analysis of the housekeeping gene encoding the a-subunit of bacterial phenylalanyl-tRNA synthase (pheS). This polyphasic approach allowed the reliable identification of 11 L. kefiranofaciens, 5 Lactobacillus paracasei, 4 Lactobacillus kefiri and 2 Lactobacillus parakefiri isolates. Isolated L. kefiranofaciens strains produced polysaccharide in straindependent concentrations and EPS produced by them also differed in the degree of polymerization. The isolation and accurate identification of L. kefiranofaciens is relevant taking into account the important role of this microorganism in the grain ecosystem as well as its potential application as starter in food fermentations.